2015
DOI: 10.1007/s11011-015-9775-9
|View full text |Cite
|
Sign up to set email alerts
|

Frontal white matter changes and aggression in methamphetamine dependence

Abstract: Chronic methamphetamine (MA) use can lead to white matter (WM) changes and increased levels of aggression. While previous studies have examined WM abnormalities relating to cognitive impairment, associations between WM integrity and aggression in MA dependence remain unclear. Diffusion Tensor Imaging (DTI) was used to investigate WM changes in 40 individuals with MA dependence and 40 matched healthy controls. A region of interest (ROI) approach using tract based spatial statistics (TBSS) in FSL was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 60 publications
1
8
1
Order By: Relevance
“…In contrast to several other studies that found lower than normal FA in several white matter regions of Meth users (Chung et al 2007; Alicata et al 2009; Kim et al 2009; Tobias et al 2010), the current study and another recent study (Lederer et al 2016) did not find group differences in FA in white matter structures. These discrepancies may be related to the different methodologies used or differences in the cohorts evaluated.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to several other studies that found lower than normal FA in several white matter regions of Meth users (Chung et al 2007; Alicata et al 2009; Kim et al 2009; Tobias et al 2010), the current study and another recent study (Lederer et al 2016) did not find group differences in FA in white matter structures. These discrepancies may be related to the different methodologies used or differences in the cohorts evaluated.…”
Section: Discussioncontrasting
confidence: 99%
“…In the white matter tracts, current Meth users consistently had higher AD than past Meth users with prolonged abstinence, which is consistent with the higher than normal MD in the genu of the corpus callosum of recently abstinent Meth users (Lederer et al 2016). Higher AD in white matter tracts indicates greater water diffusion along the axons, which is typically observed during acute inflammation, with increased cytokines (Singh et al 2016) and fluid leaking into myelin space causing axonal swelling (Kimura-Ohba et al 2016), or from loss of axonal fibers (Hikishima et al 2015).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Disrupted frontal white matter integrity is linked with impulsivity (25) and inhibition (35) in meth use disorder. Meth dependents also display structural abnormalities in the genu of the corpus callosum (138,139), a white matter tract which carries fibers originating from the PFC. Poorer corpus callosum integrity is associated with impaired inhibition (140,141) and impulse control (38).…”
Section: Inhibitory Controlmentioning
confidence: 99%
“…WM fills nearly half of the human brain, provides connections between regional or distant areas (Fields 2008b), and plays a critical role in cognition and learning (Fields 2008a). Cross-sectional diffusion tensor imaging (DTI) studies have revealed that microstructural abnormalities in fronto-striatal network (Alicata et al 2009;Chung et al 2007;Lyoo et al 2015;Tobias et al 2010) and corpus callosum (Kim et al 2009;Salo et al 2009;Tobias et al 2010) in chronic MA users were associated with cognitive function impairments (Chung et al 2007;Kim et al 2009) or clinical symptoms (Lederer et al 2016;Tobias et al 2010). Uhlmann et al (2016) reported a positive correlation between WM integrity and MA abstinence time in several major WM tracts.…”
Section: Introductionmentioning
confidence: 99%